Power Relations Between Actors in Coffee Agroforestry in Rural West Java: A Political Ecology Study - Rezeki, Evi Sri; Abdoellah, Oekan S.; Mulyanto, Dede (Sosioglobal : Jurnal Pemikiran dan Penelitian Sosiologi, 2026)
ABSTRACTThis article examines the coffee agroforestry system in West Java not merely as an environmental conservation strategy, but as an arena of contested power relations. The study aims to analyze power relations in the form of social relations of land and tree production, labor, and capital through a political ecology and actor-oriented framework. Drawing on an ethnographic approach, the research is based on participatory observation and in-depth interviews with farmers, laborers, environmental activists, policymakers, and local capital providers. The findings show that tree ownership functions as a primary claim over space amid tenure insecurity. Relations between formal landowners, cultivators/farmers, and laborers are not only hierarchical but also ambivalent. Farmers deploy everyday forms of resistance and survival strategies such as intercropping vegetables, refusing to pay profit-sharing or rent, ceb-cul arrangements, pruning coffee trees, and killing shade trees. The study concludes that coffee agroforestry is not simply a conservation practice, but a contested socio-political space. It calls for greater recognition of farmers’ rights and more equitable redistribution of power.Keywords: Power Relations; Coffee Agroforestry; Social Relations Of Production; Political Ecology; Ethnographic. ABSTRAKArtikel ini mengkaji sistem agroforestri kopi di Jawa Barat tidak hanya sebagai strategi konservasi lingkungan, tetapi juga sebagai arena kontestasi kekuasaan. Penelitian ini bertujuan menganalisis relasi kuasa dalam bentuk relasi sosial produksi lahan serta pohon, tenaga kerja, dan modal menggunakan kerangka pemikiran ekologi politik dan berorientasi aktor. Pendekatan etnografis penelitian ini didasarkan pada observasi partisipatif dan wawancara mendalam dengan petani, buruh tani, aktivis lingkungan, pemangku kebijakan, dan pemodal lokal. Hasil penelitian menunjukkan bahwa kepemilikan pohon berfungsi sebagai klaim utama atas ruang di tengah ketidakpastian tenurial lahan. Relasi antara pemilik lahan formal, penggarap, dan buruh bukan hanya bersifat hirarkis, tetapi juga bersifat ambivalen. Petani kecil mengembangkan berbagai bentuk perlawanan sehari-hari dan strategi bertahan hidup seperti tumpangsari sayuran, menolak membayar bagi hasil dan sewa, sistem ceb-cul, pemangkasan pohon kopi, dan mematikan pohon penaung. Studi ini menyimpulkan bahwa agroforestri kopi bukan sekadar praktik konservasi, tetapi ruang sosial-politik yang diperebutkan. Studi ini menyarankan pengakuan yang lebih besar terhadap hak-hak petani kecil dan kebijakan redistribusi kuasa yang adil.Kata kunci: Agroforestri Kopi; Relasi Sosial Produksi; Relasi Kekuasaan; Ekologi Politik; Etnografi